A Course In Wood Turning - Milton, Archie Seldon, 1887-; Wohlers, Otto K., 1896?- (Salt Lake City, UT : Project Gutenberg, 2005)
"A Course In Wood Turning" by Archie S. Milton and Otto K. Wohlers is a practical, instructional guide written in the early 20th century. This publication serves as a resource for educators and students interested in the craft of wood turning, a process pivotal in shaping various wooden objects and furniture elements. The text is designed to provide a comprehensive understanding of both theoretical principles and hands-on techniques essential for mastering wood turning. The book is divided into two main sections: spindle turning and face-plate turning, outlining various exercises and projects that build on one another to enhance skill development. It covers a wide array of topics, including the care of lathes, the proper handling of tools, and detailed instructions for various techniques like spiral turning and different cut types. Each chapter guides readers through exercises designed to cultivate precise movements and control, culminating in complex projects like vases and furniture parts. The text not only aims to impart technical skills but also emphasizes the artistic aspects of design, urging students to appreciate aesthetics and create functional yet beautiful objects. (This is an automatically generated summary.)
Release date is 2005-03-25
Produced by Jason Isbell and the PG Online Distributed Proofreading Team
Keywords: Turning (Lathe work); Woodwork